The Singapore legal system – History, theory and practice - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 2000)
Law is central to order and stability and, without order and stability, societal as well as economic viability (let alone progress) are impossible The alternative is 'rule of man', and all the dangers of fallibility and (consequently) despotism that that entails. One central difficulty has, of course, been the maintenance of the argument that law is consonant with objective truth for if the law does not in fact possess this quality, then the 'rule of law' turns out to be the 'rule of man' after all. However, it is difficult, on rational grounds at least, to reject the concept of objectivity without undermining the very basis of that rejection itself- unless one is prepared to premise one's argument (for such rejection) on blind faith as well as to affirm one's argument whilst rejecting any claim to the truth of that argument itself It is of course true that even if the law otherwise possesses objectivity, it must still be applied by persons and that could also result in the 'rule of man'. However, one central tenet underlying the 'rule of law' is the idea that the law itself constrains those applying and administering the law itself: although this idea is itself also not without controversy.2 Further, the very concept of the 'rule of law' itself has been traditionally perceived as ensuring procedural (as opposed to substantive) fairness; in other words, and to put it very crudely, a fair procedure does not necessarily entail a fair resulf - although the present writer would submit that the distinction between procedure and substance is oftimes an artificial one and that, as Professor Patrick Atiyah has pertinently pointed out in the context of contract law, procedural and substantive fairness often impact on, as well as interact with, each other.' The very brief discussion thus far reveals complex conceptual as well as practical problems that cannot really be dealt with within the more modest ambit of the present paper. It is submitted that whatever view one adopts ofthe objectivity (or otherwise) of the law in general and the precise nature of the 'rule of law' in particular, very few people - particularly in Singapore - would seriously controvert the need for 'rules'. Indeed, the popular perception (both within the country and without) has been precisely that Singapore is a very rule-oriented society indeed.